Relevance of Intestinal Microbiota in Immunoglobulin A Vasculitis With Abdominal Involvement - Zhang, Linqian; Jia, Xinyi; Lai, Panjian; Wang, Kang; Bao, Yunguang; Li, Xiaobing (Frontiers in Pediatrics, 2022)
Immunoglobulin A vasculitis (IgAV) is a very common condition in children. Background: We explored the intestinal microbiota changes in IgAV with abdominal involvement (IgAV-GI) at the acute and convalescent stages and evaluated the role of intestinal microbiota in the clinical course of patients with IgAV. Methods: A total of 37 patients with IgAV were included, and the control group comprised 37 age- and sex-matched healthy children. Stool samples were collected from 28 children with IgAV-GI (19 in the acute stage and 9 in the recovery stage) and from nine children with non-abdominal involvement. Faecal specimens were selected and DNA was obtained using an extraction kit which was then subjected to high-throughput sequencing and analysis. Results: There was no significant difference in the community structure of the intestinal microbiota among the IgAV-GI acute, IgAV-GI convalescence, and IgAV-non-GI stages. The abundance of Veillonella in the acute stage of IgAV-GI was significantly higher than that in IgAV-non-GI and convalescence stages, and Ruminococcus was the most abundant in IgAV-GI convalescence. The α-diversity of children with IgAV was significantly lower than that of healthy children, and healthy children had higher intestinal microbiota richness and more evenly distributed species. In terms of changes in intestinal microbial diversity in patients with IgAV at the genus level, obligate anaerobes including Bifidobacterium, Prevotella, Coprobacter, Prevotella_9, Blautia, Romboutsia, Parabacteroide, Subdoligranulum, and Roseburia were significantly reduced, and the enrichment of facultative anaerobe was represented by Bacteroides, Lachnoclostridium, and Alistipe. Conclusions: Different bacterial species may be involved in the pathogenesis of different types of IgAV-GI. Differences were observed in the intestinal microbiota between healthy children and children with IgAV.